2005
DOI: 10.2108/zsj.22.1011
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Specific and Age-Dependent Expression of Insulin-like Growth Factor-I (IGF-I) mRNA Variants: IGF-IA and IB mRNAs in the Mouse

Abstract: -Insulin-like growth factor-I (IGF-I) gene generates several IGF-I mRNA variants by alternative splicing. Two promoters are present in mouse IGF-I gene. Each promoter encodes two IGF-I mRNA variants (IGF-IA and IGF-IB mRNAs). Variants differ by the presence (IGF-IB) or absence (IGF-IA) of a 52-bp insert in the E domain-coding region. Functional differences among IGF-I mRNAs, and regulatory mechanisms for alternative splicing of IGF-I mRNA are not yet known. We analyzed the expression of mouse IGF-IA and IGF-IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…Other studies have indicated that the locally acting iGF1 isoform also has neuroprotective effects and protects cardiomyocytes from hypertrophic and oxidative stress (9,23,24). Ohtsuki et al, using the pcr method, demonstrated that iGF1Ea mrna was more abundant than iGF1Eb mrna in a number of organs (uterus, ovary, liver and kidney) in the mouse, and was both organ specifically and temporally regulated (25). additionally, it has been suggested that E-peptides modulate the cell entry of mature iGF1 (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have indicated that the locally acting iGF1 isoform also has neuroprotective effects and protects cardiomyocytes from hypertrophic and oxidative stress (9,23,24). Ohtsuki et al, using the pcr method, demonstrated that iGF1Ea mrna was more abundant than iGF1Eb mrna in a number of organs (uterus, ovary, liver and kidney) in the mouse, and was both organ specifically and temporally regulated (25). additionally, it has been suggested that E-peptides modulate the cell entry of mature iGF1 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of studies have focused on the identification of different IGF1 isoforms and the evaluation of their functional significance (9,(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen stimulates Igf1 transcription (Murphy et al, 1987;Ghahary et al, 1990;Kapur et al, 1992;Zhou et al, 1994;Ohtsuki et al, 2005), and high levels of circulating estrogen at proestrus induced high Igf1 mRNA levels. Igf1r mRNA levels also changed during the estrous cycle; they were high at diestrus and low during proestrus and estrus, suggesting that the responsiveness of endometrial cells to IGF1 depends upon the stage of the estrous cycle, and possibly upon levels of estrogen and progestin.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA sequence was obtained from GenBank (accession number; NM_011434), and forward and reverse primers were designed to span different exons to avoid genomic DNA amplification. Quantitative measurement was performed by establishing a linear amplification curve from serial dilutions of cloned mouse CuZnSOD mRNA and GAPDH mRNA [21]. The amount of CuZn-SOD mRNA was normalized to the amount of GAPDH mRNA.…”
Section: Rna Extraction Cdna Synthesis and Quantitative Realtime Pcmentioning
confidence: 99%